A SZERvezet - Orosz, Csilla (Hungary : Pesty Fekete Doboz, 1994)
Television documentary about the history of the Hungarian Desk of Radio Free Europe - Radio Liberty (RFE / RL). Among others Laszlo Kasza and Geza Ekecs, former RFE Hungarian Desk editors remember about the operations and the programs of RFE-RL. The role of RFE in the 1956 revolution and in the 1989 change of regimes are discussed.
Formerly in 317-0-1.
Duration: 00:58:00
Keywords: Documentary films